GAYA BAHASA PADA LIRIK-LIRIK LAGU KARYA IWAN FALS DALAM ALBUM 50:50 2007 - Hudaa, Syihaabul (Program Studi Magister Linguistik Terapan UNJ, 2017)
ABSTRACT This study aims to find the type, function, and style any meaning contained in the lyrics Iwan Fals Album 50-50, 2007. This study examines every song contained therein, as well as classifying according to the type of style, as well as reviewing function, and know the meaning to be conveyed through the lyrics of the song. This study used a qualitative approach using content analysis method. Researchers first collected data in the form of song, then perform an analysis of the lyrics on the album 50:50 in 2007 to find a function of the type of style that is discovered, and the meaning of what is contained in it. The results of the study researchers found that in this 2007 album 50:50 was found three types of style groups: (1) Comparative Languages force, (2) the language style of contention, (3) the language style affirmation. From the overall style of the existing language, the author is more dominant in the style of metaphorical language in conveying the message to be conveyed through the lyrics of the song. Research on 50:50 Album Iwan Fals work shows that, more often using metaphorical language style. This can be seen in the table above that the style of language is more dominant metaphor used by the results of 28.9% from 13 emerging data from a total of 45 data that has been discovered by researchers. The use of stylistic metaphors in the lyrics Iwan Fals, are actually trying to portray through the lyrics as a form that seeks comparing with the actual situation. Keywords: language style, type, functions, meaning